Hemodynamic Changes Caused by Multiple Stenting in Vertebral Artery Fusiform Aneurysms: A Patient-Specific Computational Fluid Dynamics Study - Lv, N.; Cao, W.; Larrabide, I.; Karmonik, C.; Zhu, D.; Liu, J.; Huang, Q.; Fang, Y. (American Journal of Neuroradiology, 2017)
BACKGROUND AND PURPOSE: The multiple stent placement technique has largely improved the long-term outcomes of intracranial fusiform aneurysms, but the hemodynamic mechanisms remain unclear. In this study, we analyzed the hemodynamic changes caused by different stent-placement strategies in patient-specific models using the computational fluid dynamics technique, aiming to provide evidence for clinical decision-making.MATERIALS AND METHODS: Ten vertebral artery fusiform aneurysms were included, and their patient-specific computational fluid dynamics models were reconstructed. A fast virtual stent placement technique was used to simulate sequential multiple stent placements (from a single stent to triple stents) in the vertebral artery fusiform aneurysm models. Hemodynamic parameters, including wall shear stress, pressure, oscillatory shear index, relative residence time, and flow pattern, were calculated and compared among groups with different numbers of stents.RESULTS: Virtual stents were deployed in all 10 cases successfully, consistent with the real stent configuration. Wall shear stress decreased progressively by 7.2%, 20.6%, and 25.8% as the number of stents increased. Meanwhile, relative residence time and pressure increased on average by 11.3%, 15.4%, and 45.0% and by 15.7%, 21.5%, and 28.2%. The oscillatory shear index showed no stable variation trend. Flow patterns improved by weakening the intensity of the vortices and displacing the vortex center from the aneurysmal wall.CONCLUSIONS: Stent placement modifies hemodynamic patterns in vertebral artery fusiform aneurysms, which might favor thrombosis formation in the aneurysmal sac. This effect is amplified with the number of stents deployed. However, a potential risk of rupture or recanalization exists and should be considered when planning to use the multiple stent placement technique in vertebral artery fusiform aneurysms.CFDcomputational fluid dynamicsOSIoscillatory shear indexRRTrelative residence timeVAFAvertebral artery fusiform aneurysmWSSwall shear stress